(untitled) (Brazilian Journal of Radiation Sciences, 2019)
The analyzes carried out in this work aims to contribute to the discussion about the ceramic objects founded in Monte Castelo’s sambaqui located at south-west Amazonia. The first study accomplished by Miller in 1980 suggests that this archaeological site is inserted in the oldest contexts of production of ceramics in the Amazon. Until today, there aren’t any physical and chemical analysis studies in this ceramics and this kind of studies may help archaeological studies performed at the sambaqui. With this purpose, this work presents a preliminary study of chemical characterization of eighty-four ceramic samples using instrumental neutron activation analysis (INAA) by means of the determination of Na, K, La, Sm, Yb, Lu, U, Sc, Cr, Fe, Co, Zn, Rb, Cs, Ce, Eu, Hf and Th. With the purpose to study the similarity/dissimilarity between the samples, cluster and discriminant analysis were used. The results showed the existence of three different chemical groups whose dating ranging 3000 b.P. to 1500 b.P. that are in agreement with the archaeological studies made by Miller and suggest Bacabal’s phase as the oldest ceramist culture in the Southwest of the Amazon.